2023
DOI: 10.1002/jso.27155
|View full text |Cite
|
Sign up to set email alerts
|

Salvage surgery in lung cancer following definitive therapies

Abstract: Salvage surgery refers to operative resection of persistent or recurrent disease in patients initially treated with intention-to-cure nonoperative management. In non-small-cell lung cancer, salvage surgery may be effective in treating selected patients with locally progressive tumors, recurrent local or locoregional disease, or local complications after nonoperative therapy. Importantly, those patients who may be candidates for salvage surgery are evolving, in terms of disease stage as well as the types of att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 74 publications
(225 reference statements)
1
6
0
Order By: Relevance
“…The efficacy and safety of salvage thoracic operations have not yet been fully elucidated [ 17 ]. The present definition of salvage surgery for lung cancer is younger than 20 years and refers almost exclusively to non-small cell lung cancer (NSCLC) [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], but it is important to underline that the same definition was proposed for and the same procedures were performed in SCLC, as presented above; therefore, the theoretical and practical information is resumed as follows: Salvage surgery for an emergent complication, as a life-saving procedure, performed for an event that occurred during the natural history of the tumor or as a complication during oncological treatment, including SBRT, with curative or palliative intent: massive hemoptysis, lung abscess, empyema, broncho–pleural fistula; Salvage surgery after definitive (full-dose) chemo–radiation therapy/after previous local (SABR) or general treatment (ex. targeted therapy): residual/persistent localized disease, relapsed tumor/recurrence after complete response, cases judged to be contraindicated for chemotherapy or definite radiation therapy due to severe comorbidities, despite a clinical diagnosis of NSCLC stage IIIA, IIIB, or IV disease initially, delayed decision to convert to a trimodal approach; Salvage surgery for progression under chemotherapy; Salvage surgery for oligo-metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and safety of salvage thoracic operations have not yet been fully elucidated [ 17 ]. The present definition of salvage surgery for lung cancer is younger than 20 years and refers almost exclusively to non-small cell lung cancer (NSCLC) [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], but it is important to underline that the same definition was proposed for and the same procedures were performed in SCLC, as presented above; therefore, the theoretical and practical information is resumed as follows: Salvage surgery for an emergent complication, as a life-saving procedure, performed for an event that occurred during the natural history of the tumor or as a complication during oncological treatment, including SBRT, with curative or palliative intent: massive hemoptysis, lung abscess, empyema, broncho–pleural fistula; Salvage surgery after definitive (full-dose) chemo–radiation therapy/after previous local (SABR) or general treatment (ex. targeted therapy): residual/persistent localized disease, relapsed tumor/recurrence after complete response, cases judged to be contraindicated for chemotherapy or definite radiation therapy due to severe comorbidities, despite a clinical diagnosis of NSCLC stage IIIA, IIIB, or IV disease initially, delayed decision to convert to a trimodal approach; Salvage surgery for progression under chemotherapy; Salvage surgery for oligo-metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Centrally located lung cancer with a massive tumor burden is challenging for achieving appropriate surgical traction and safe dissection. Considering the difficulty of sparing hilar vessels, the blood loss in salvage pulmonary surgery ranges from 0 to 4400 mL [ 21 ]. The CUSA can be used for structural dissection in cases showing adhesion around the hilar and mediastinum.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative complications developed in 40.9% of the patients in our study, including six in the non-CUSA group and three in the CUSA group, without showing a statistically significant difference between groups. Some studies have reported complication rates of 30–57% [ 21 , 40 ]. In our study, age was an independent risk factor associated with all complications in multivariate logistic regression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to several studies, the primary methods used to treat tumors at the moment are surgical removal, pharmacological chemotherapy, radiotherapy, targeted therapy, immunotherapy, and traditional Chinese medicine ( Bae et al, 2023 ; Eisenberg et al, 2023 ; Lazaroff and Bolotin, 2023 ; Song et al, 2023 ). Additionally, it is believed that medicinal chemotherapy is still the primary method of tumor treatment, in accordance with a range of different criteria and consensus both domestically and internationally ( Chen et al, 2022 ; Reig et al, 2022 ; Strazzabosco et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%